2018
DOI: 10.1080/15389588.2017.1381337
|View full text |Cite
|
Sign up to set email alerts
|

Does obesity affect the position of seat belt loading in occupants involved in real-world motor vehicle collisions?

Abstract: The results from this study demonstrated that anterior displacement of the radiographic seat belt sign but not superior displacement increased with higher BMI. These results suggest that obesity may worsen horizontal position but not the vertical position of the lap belt loading during real-world frontal MVCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
5
2
Order By: Relevance
“…The reason for the difference between our results and Hartka et al 25 may be the difference in posture when measuring the X-value and Z-value. Their CT study would have been measured in the supine position, but our study used a coordinate system in the sitting position.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The reason for the difference between our results and Hartka et al 25 may be the difference in posture when measuring the X-value and Z-value. Their CT study would have been measured in the supine position, but our study used a coordinate system in the sitting position.…”
Section: Discussioncontrasting
confidence: 99%
“…About SBS location, Hartka et al measured the position of the SBS in actual car accident patients on CT, and reported that the X-value was greater in obese people while the Z-value did not change much 25 . In contrast, at the laboratory level, Reed et al measured the lap belt position, and reported that a 10 kg/cm 2 increase in BMI resulted in a 43 mm anterior and 21 mm superior position 26 .…”
Section: Discussionmentioning
confidence: 99%
“…13 The extended webbing length combined with greater body mass increases the counteractive restraint force applied to the occupant which could contribute to the increased incidence of seat belt markings. 1315…”
Section: Discussionmentioning
confidence: 99%
“…A static measurement of belt fit was conducted in literature. 3,4,8,9 Particularly, how the lap belt position is altered by obesity was investigated. Obesity moved the initial lap belt position further anterior-superior to the ASIS.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity introduces slack between the seatbelt and the underlying bony structure, because of a thicker layer of subcutaneous adipose tissue, which reduces seatbelt functionality. A static measurement of belt fit was conducted in literature 3,4,8,9 . Particularly, how the lap belt position is altered by obesity was investigated.…”
Section: Introductionmentioning
confidence: 99%